Emerging Aeromonas Species Infections and Their Significance in Public Health. (4th June 2012) - Igbinosa, Isoken H.; Igumbor, Ehimario U.; Aghdasi, Farhad; Tom, Mvuyo; Okoh, Anthony I.
Abstract : Aeromonas species are ubiquitous bacteria in terrestrial and aquatic milieus. They are becoming renowned as enteric pathogens of serious public health concern as they acquire a number of virulence determinants that are linked with human diseases, such as gastroenteritis, soft-tissue, muscle infections, septicemia, and skin diseases. Proper sanitary procedures are essential in the prevention of the spread of Aeromonas infections. Oral fluid electrolyte substitution is employed in the prevention of dehydration, and broad-spectrum antibiotics are used in severe Aeromonas outbreaks. This review presents an overview of emerging Aeromonas infections and proposes the need for actions necessary for establishing adequate prevention measures against the infections.